Non-permanent migration in Rancang Welak Village community - Afat, Gordianus; Kusufa, Roni Alim Ba’diya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Non-permanent mobility among residents of rural areas has become a notable phenomenon, particularly driven by economic factors and advancements in destination areas. In Racang Welak Village, West Manggarai Regency, the residents engage in non-permanent mobility seeking better economic opportunities and attracted by progress in destination areas. Methods: This descriptive qualitative research aims to explore the factors influencing non-permanent mobility among residents of Racang Welak Village. Data collection methods included observation, interviews, and documentation. The study focused on residents who were engaged in non-permanent mobility, particularly seasonal farmers. Results: The findings revealed that residents, especially seasonal farmers, felt their needs were unmet in the village and sought information about job opportunities elsewhere. As a result, they engaged in non-permanent mobility, primarily driven by economic factors. The residents undertook mobility due to push factors from their village and pull factors from destination areas, particularly economic opportunities and advancements. Conclusions: The research concludes that economic factors play a significant role in driving non-permanent mobility among residents of Racang Welak Village. The allure of economic opportunities and progress in destination areas encourages residents to migrate non-permanently. This study provides insights into the factors influencing non-permanent mobility in rural areas and highlights the importance of economic considerations in migration decisions.